Pola Komunikasi Organisasi Alumni Syubanul Wathon (Aswa) Balapan dalam Meningkatkan Ukhuwah Islamiyah - Amelia, Amelia; Chikmatul Masruroh; Firdausin Nurul Milati; Anaz Azhimi Qalban (MUKASI: Jurnal Ilmu Komunikasi, 2024)
Organizational communication patterns in the Aswa Balapan organization are related to the implementation of improving the intertwined ukhuwah islamiyah. This communication pattern is intended to understand that every organization must have its own communication pattern for the continuity of its members. So it is necessary to have the right communication pattern in Aswa Balapan. This study intends to examine the extent to which the communication patterns of the Aswa Balapan organization as an effort to increase the sense of ukhuwah islamiyah among members based on the analysis of the interactive model of the Miles and Huberman theory with descriptive qualitative methods and data collection techniques in the form of interviews, observation and documentation. The results of the study, namely, communication patterns in the Balapan Syubanul Wathon Alumni (Aswa) organization are supported by various types of communication patterns ranging from chain, circle, wheel, and total channel patterns. The existence of symbolic interaction and the right communication flow in Aswa Balapan through various activities, such as makrab, open together, competition workshop, Aswa Balapan bersholawat. Symbolic interaction also plays an important role in building ukhuwah islamiyah bonds among Aswa Balapan members.